National pediatric palliative care needs from hospital deaths - Khalid, Farah; Chong, Lee Ai (Medknow Publications, 2019)
Objective: The objective of this study was to estimate palliative care needs and to describe the cohort of children with life-limiting illnesses (LLI) dying in hospitals. Design: This study was a retrospective cohort study. The national hospital admissions database was reviewed and children who had died who had life-limiting illnesses were identified. Setting: This study was conducted at Ministry of Health hospitals, Malaysia. Patients: Children aged 18 years and below who had died between January 1, 2012 and December 31, 2014. Main Outcome Measures: Life-limiting diagnoses based on Hain et al.'s directory of LLI or the ACT/RCPCH categories of life-limiting disease trajectories. Results: There were 8907 deaths and 3958 (44.4%) were that of children with LLI. The majority, 2531 (63.9%) of children with LLI were neonates, and the most common diagnosis was extreme prematurity <28 weeks with 676 children (26.7%). For the nonneonatal age group, the median age at admission was 42 months (1-216 months). A majority, 456 (32.0%) had diagnoses from the ICD-10 chapter 'Neoplasms' followed by 360 (25.3%) who had a diagnoses from 'Congenital malformations, deformations, and chromosomal abnormalities' and 139 (9.7%) with diagnoses from 'Disease of the nervous system.' While a majority of the terminal admissions were to the general ward, there were children from the nonneonatal age group, 202 (14.2%) who died in nonpediatric wards. Conclusion: Understanding the characteristics of children with LLI who die in hospitals could contribute toward a more efficient pediatric palliative care (PPC) service development. PPC service should include perinatal and neonatal palliative care. Palliative care education needs to extend to nonpediatric healthcare providers who also have to manage children with LLI. © 2019 Indian Journal of Palliative Care | Published by Wolters Kluwer-Medknow.